Acupuncture for systemic therapy-associated insomnia in patients with breast cancer: a systematic review and meta-analysis of randomized controlled trials - Gao, Lingling; Sun, Ying; Luo, Tianyu; Chen, Huiying; Huang, Shan; Zhu, Ling; Ye, Meixia (Frontiers in Oncology, 2025)
BackgroundSystemic therapy-associated insomnia is highly prevalent among patients with breast cancer. However, no meta-analysis has explored the efficacy of acupuncture for Systemic therapy-associated insomnia among patients with cancer.MethodsAccording to the PRISMA Statement, randomized controlled trials (RCTs) through April 2024 were identified and extracted from PubMed, Embase, and the Cochrane CENTRAL Register of Controlled Trials. The quality of the RCTs was assessed using the Cochrane Systematic Review Handbook 5.1 and its recommended risk-of-bias assessment tool. Two independent investigators screened and extracted the data and performed statistical analysis using RevMan5.3.ResultsOf the total 411 studies identified, 4 RCTs were analyzed. The meta-analysis revealed that acupuncture significantly improved the total sleep time and sleep efficiency relative to wait-list control or sham EA among patients with breast cancer experiencing insomnia after systemic therapy (mean difference [MD] 29.86, 95% confidence interval [CI] 16.20–43.51, P < 0.0001 and MD 4.56, 95% CI 1.84–7.29, P = 0.001), reduced the pittsburgh sleep quality index (PSQI) relative to wait-list control or sham EA with an MD of −0.87 (95% CI −1.60 to -0.15, P = 0.02, I2 = 25%) in 4 weeks and an MD of −0.82 (95% CI −1.60 to -0.04, P = 0.04, I2 = 12%) in 8 weeks, and reduced the hospital anxiety and depression scale (HADS)-anxiety both in 4 weeks with an MD of −0.85 (95% CI −1.42 to -0.27, P = 0.004, I2 = 0%) and in 8 weeks with an MD of −0.94 (95% CI −1.56 to −0.32, P = 0.003, I2 = 0%. However, no significant differences in insomnia severity index (MD −2.15, 95% CI −5.07 to 0.78, P = 0.15 and MD −1.48, 95% CI −3.91 to 0.94, P = 0.23), and HADS-depression (MD −0.67, 95% CI −2.32 to 0.99, P = 0.43 and MD −0.63, 95% CI −2.39 to 1.12, P = 0.48) in 4 and 8 weeks were observed between the acupuncture group and the wait-list control or sham EA group.ConclusionAcupuncture has a great potential to be used in the management of systemic therapy-associated insomnia in patients with breast cancer. More studies with rigorous designs and larger sample sizes are warranted to verify the efficacy and safety of acupuncture for insomnia among patients with breast cancer.